Multiple nicotinic acetylcholine receptor genes are expressed in goldfish retina and tectum - Cauley, K (J Neurosci, 1990)
cDNAs encoding a novel nAChR structural subunit (GFn alpha-3) and a ligand-binding subunit (GF alpha-3) have been isolated from a goldfish retina cDNA library. The protein encoded by GFn alpha-3 shares 88% amino acid similarity with that encoded by GFn alpha-2, a structural subunit gene previously identified to be expressed in this system (Cauley et al., 1989). The ligand-binding subunit (GF alpha-3) is likely the goldfish homolog of the rat alpha-3 gene (Boulter et al., 1986). Northern blots and S1 protection experiments show that GFn alpha- 3 and GF alpha-3 genes are expressed in retina and brain. GFn alpha-3 identifies multiple RNAs differing in their 3′ untranslated regions. In situ hybridization analysis demonstrates GFn alpha-3, GFn alpha-2, and GF alpha-3 expression by cells of the retinal ganglion cell layer. Unlike GFn alpha-2 and GF alpha-3, GFn alpha-3 is expressed at highest levels by cells of the retina's inner nuclear layer. In the optic tectum, both GF alpha-3 and GFn alpha-3 genes are expressed by cells of the periventricular zone, as well as more superficial layers. These results suggest the presence of multiple nAChR systems in retina and tectum. In addition, they indicate that tectal nAChRs may arise from remote (ganglion cell) as well as local (tectal cell) synthesis.